2010
DOI: 10.1097/mbc.0b013e328338948f
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide releasing molecule-2 increases fibrinogen-dependent coagulation kinetics but does not enhance prothrombin activity

Abstract: We have previously determined that tricarbonyldichlororuthenium (II) dimer (CORM-2) increases plasma clot velocity of formation and strength by enhancing thrombin-fibrinogen interactions as determined by thrombelastography. The purpose of the present investigation was to further define the nature of CORM-2 interaction with prothrombin and fibrinogen by exposing purified proteins to CORM-2 or generating protein concentration-response curves in the absence or presence of CORM-2. Purified prothrombin was exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…This is also confirmed by previous studies by Soni et al 13 Those authors showed that CORM-3 decreased plasma PAI-1 levels, but in their model CORM-3 was administered by guest on May 11, 2018 http://atvb.ahajournals.org/ Downloaded from during a 10-minute infusion at 3 mg/kg (which is equivalent to 100 µmol/kg of CORM-3), thus the CO, which was liberated, could have been in contact with the released from platelets PAI-1. However, Nielsen et al 11,12,44 have shown that CORM-2 inhibits fibrynolysis. Nevertheless, their experiments were preformed only in vitro using this lipid-soluble and fast metalcontaining CO releaser, which makes it difficult to compare with our results obtained with water-soluble CORMs in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also confirmed by previous studies by Soni et al 13 Those authors showed that CORM-3 decreased plasma PAI-1 levels, but in their model CORM-3 was administered by guest on May 11, 2018 http://atvb.ahajournals.org/ Downloaded from during a 10-minute infusion at 3 mg/kg (which is equivalent to 100 µmol/kg of CORM-3), thus the CO, which was liberated, could have been in contact with the released from platelets PAI-1. However, Nielsen et al 11,12,44 have shown that CORM-2 inhibits fibrynolysis. Nevertheless, their experiments were preformed only in vitro using this lipid-soluble and fast metalcontaining CO releaser, which makes it difficult to compare with our results obtained with water-soluble CORMs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CO paradoxically increases the formation of fibrin 11 and inhibits fibrinolysis 12 in in vitro studies, whereas it exerts antithrombotic effect in vivo, which involves activation of fibrinolysis. 13 Notably, a direct role of CO gas in mitigating the process of thrombosis was assessed by True et al 14 These authors found that Hmox-1 knockout mice display a prothrombotic phenotype characterized by damage of endothelial cells and apoptosis, platelet activation, elevation in both tissue factor and von Willebrand factor, and reactive oxygen species.…”
mentioning
confidence: 99%
“…were exposed to CORM-2 [51][52][53][54][55][56][57] In order to further characterize the mechanism by which CO enhanced coagulation, experiments involving isolated exposure of prothrombin [58] or fibrinogen [59] to CORM-2 were performed, with the purified protein function assessed in prothrombin or fibrinogen deficient plasmas, respectively. These works lead to the determination that only fibrinogen was affected by CO [58,59], and additional work utilizing mass spectrometry [60] demonstrated that protease digestion of fibrinogen was modified by exposure to CO. More importantly, it was noted that a heme group(s) was present in the fibrinogen digest samples, and following exposure of human plasma to compounds that either produced a carboxyheme or metheme state, plasma strength was increased or decreased respectively, indicative of heme-based modulation of fibrinogen function [60].…”
Section: In Vitro and Preclinical Evidence That Co Is A Procoagulant mentioning
confidence: 99%
“…These works lead to the determination that only fibrinogen was affected by CO [58,59], and additional work utilizing mass spectrometry [60] demonstrated that protease digestion of fibrinogen was modified by exposure to CO. More importantly, it was noted that a heme group(s) was present in the fibrinogen digest samples, and following exposure of human plasma to compounds that either produced a carboxyheme or metheme state, plasma strength was increased or decreased respectively, indicative of heme-based modulation of fibrinogen function [60]. Exploiting this newfound redox chemistry of fibrinogen, an assay was devised to determine the presence of CO bound to fibrinogen, named carboxyhemefibrinogen (COHF), as a modification of thrombelastographic methodology [61].…”
Section: In Vitro and Preclinical Evidence That Co Is A Procoagulant mentioning
confidence: 99%
See 1 more Smart Citation